Primary Extrahepatic Bile Duct Carcinoids. Issue 2 (1996) - Belli, Giulio; Rotondano, Gianluca; D'Agostino, Alberto; Marano, Ines
Abstract : Biliary tact carcinoids are extremely rare: only ten cases have been reported up to now. The Authors describe a successfully treated carcinoid tumour ofthe proximal bile duct and review the literature about these rare malignancies. Despite extensive preoperative work-up, including ultrasound, CT scan and ERCP, a definite diagnosis is hardly possible prior to histologic examination of the operative or necropsy specimen. Due to the slow-growing nature and the non-aggressive behaviour of these malignancies, surgical resection followed by biliodigestive anastomosis should be the treatment of choice.